A Reconfigurable GNSS Acquisition Scheme for Time-Frequency Applications. (14th July 2008) - Borio Borio, Daniele Daniele; Lo Presti Lo Presti, Letizia Letizia
Abstract : The extreme weakness of global navigation satellite system (GNSS) signals makes them vulnerable to almost every kind of interferences that, without adequate countermeasures, can heavily compromise the receiver performance. An effective solution is represented by time-frequency (TF) analysis that has proved to be able to detect and suppress a wide class of disturbing signals. However, high computational requirements have limited the diffusion of such techniques for GNSS applications. In this paper, we propose an effective solution for the efficient implementation of TF techniques on GNSS receivers. The solution is based on the key observation that the first block of a GNSS receiver, the acquisition stage, implicitly performs a sort of TF analysis. Thus, a slight modification in the traditional acquisition scheme enables the fast and efficient implementation of TF techniques for interference detection. The proposed method is suitable for different types of acquisition scheme and its effectiveness is proved by simulations and examples on real data.